Perfumes : the guide - Turin, Luca (Viking, 2008)
An olfactory scientist and a perfume critic review more than 1,200 fragrances to identify preferred and less-recommended varieties, in a guide that introduces women's and men's fragrances and discusses the history and chemistry of perfumes.